(untitled) (Shahroud Journal of Medical Sciences, 2017)
Background: Growing evidences show that the successful treatment of pediatric obesity requires consideration not only of medical issues but also of psychological and social environmental and familial factors. Special emphasis is given to the psychological and spiritual aspects of pediatric obesity in the context of a holistic perspective. In this regard this study was conducted to determine the effectiveness of multi-faceted training focused on spiritual parenting to mothers on promoting spirituality of overweight children.Methods: In this study, 48 volunteer (24 boy students and 24 their mothers) eligible to exclude-include criteria were selected and randomly assigned into two experimental and control groups. An orientation session was held to explain the research goals and intervention. The experimental group trained, 90 minutes sessions weekly for 3 months (10 sessions), but control group did not receive any intervention. Prior to and after Training, all participant completed demographic information questionnaire and then children completed religiosity and spirituality scale for youth (rassy) scale and childrens' BMI were measured. Data analysis with 22th version of SPSS was done.Results: Data analysis with applying one-way and multivariate analysis of covariance ( ancova and mancova) revealed that Multi-faceted training focused on spiritual parenting could significantly promote the total score and faith-based coping and religious social support/activities but BMI were decreased significantly (P<0.05). Conclusions: The results showed that the multi-faceted training focused on spiritual parenting to mothers leads to promotion of spirituality scores of children with overweight. Also, it seems that the body mass index (BMI) will be reduced. This study demonstrated that spiritual parenting benefits are similar to the dietary restriction and physical activity. And it can cause weight loss and enhance spirituality in children.